Survival probability of zirconia-reinforced lithium silicate ceramic: Effect of surface condition and fatigue test load profile - Dal Piva, Amanda Maria de Oliveira [UNESP]; Tribst, João Paulo Mendes [UNESP]; Venturini, Andressa Borin; Anami, Lilian Costa; Bonfante, Estevam Augusto; Bottino, Marco Antonio [UNESP]; Kleverlaan, Cornelis Johannes (Elsevier, 2020)
Objectives: The present investigation evaluated the step stress accelerated test (SSALT) load profiles on the survival probability of a glass ceramic under two surface conditions (polished or roughened). Methods: Suprinity–ZLS blocks (Vita Zhanfabrik) were shaped into cylinders, cut in a sawing machine, and crystalized according to the manufacturer's instructions. 60 discs were obtained (Ø = 12 mm, thickness = 1.2 mm) and randomly assigned into two surface conditions: “p” polished surface (400–1200-grit SiC papers), and “r” roughened surface (200-grit SiC papers). Profilometry was performed in all discs to evaluate average surface roughness prior to flexural fatigue strength testing. 3 discs of each group were submitted to biaxial flexural strength in an universal testing machine (0.5 mm/min) and the mean load to failure (N) was calculated to determine SSALT profiles. 27 specimens per surface condition were assigned into three profiles – Mild (n = 9), Moderate (n = 9), and Aggressive (n = 9), and submitted to the fatigue test (60–320 N, 140,000 cycles at 1.4 Hz). The results were analyzed using the Kaplan-Meier and Wilcoxon tests (5%), 2-way ANOVA and Tukey test (α = 5%). Results: Kaplan-Meier and generalized Wilcoxon showed (P = 0.002) that polished groups showed higher survival probability than roughened condition (P < 0.05). A rough internal surface impacted deleteriously on the fatigue strength and reliability of ZLS ceramic. Both surface conditions were more sensitive to the aggressive profile than the other profiles, even worst for the roughened group. Regardless the load profile, 0% survival probability was observed at 384 MPa for polished condition. While for roughened, aggressive tested specimens did not survived 147 MPa followed by moderate at 312 MPa and mild at 384 MPa. The failure modes showed fracture marks originating from superficial grooves for both surface conditions. Significance: Polished specimens are sensitive to the load profile variation, confirming the effect of surface morphology on the fatigue results.
Keywords: Biaxial flexure strength; Dental materials; Fatigue; Methods; Roughness; Zirconia reinforced lithium silicate material properties